Perfil de suscetibilidade de Moraxella bovis, Moraxella bovoculi e Moraxella ovis aos antimicrobianos - Maboni, Grazieli (2013)
Infectious keratoconjunctivitis (IK), also known as pinkeye , is an ocular disease that affects cattle and sheep. In cattle, the microorganisms involved are Moraxella bovis, Moraxella bovoculi and Moraxella ovis. In sheep, the main microorganisms isolated from lesions are Mycoplasma conjuntivae, Chlamydia psittaci and M. ovis. Antibiotics are widely used in the treatement ofthis disease; therefore, to perform tests of susceptibility is essential in order to use the most effective drugs. However, few studies about the susceptibility of M. bovis, M. bovoculi and M. ovis to antibiotics are available in the literature. In Brazil, there are no studies describing the susceptibility profile of M. bovoculi and M. ovis. Susceptibility tests for M. bovis, M. bovoculi and M. ovis are routinely determined at laboratories by disk diffusion method. On the other hand, the broth microdilution method, which is the reference method, is used for Moraxella spp. with epidemiological purposes, such as, to define the antimicrobial susceptibility profiles of strains from a specific region. This dissertation aimed to determine the antimicrobial susceptibility of Brazilian strains of M. bovis, M. bovoculi and M. ovis by broth microdilution and disk diffusion for the main antimicrobials used to treat IK and, thus, to verify differences in antimicrobial susceptibility profiles of the three species of Moraxella. We also aimed to evaluate the agreement between the disk diffusion and broth microdilution method. In order to determine the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC), obtained by the broth microdilution method, and the diameter of inhibition zone, obtained by disk diffusion method, the following antimicrobials were used: ampicillin, cefoperazone, ceftiofur, cloxacillin, enrofloxacin, florfenicol, gentamicin, neomycin, oxytetracycline and penicillin. The MIC and MBC were higher for M. bovis than for M. bovoculi and M. ovis. The drugs evaluated showed good agreement between disc diffusion and the reference method, except oxytetracycline and penicillin. When analyzed the methods agreement for each Moraxella species we found lower rates of agreement, as well as, more quantities of errors in M. bovis strains. The results of this study emphasize that M. bovis, M. bovoculi and M. ovis have a different antimicrobial susceptibility profile.